2014
DOI: 10.1096/fj.13-244632
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene iASPP enhances self‐renewal of hematopoietic stem cells and facilitates their resistance to chemotherapy and irradiation

Abstract: iASPP is a member of the apoptosis-stimulating proteins of p53 (ASPP) family and negatively regulates the apoptotic function of p53. In a hematopoietic system, overexpression of iASPP results in blockage of apoptosis, which may play a role in regulating hematopoietic stem cell (HSC) numbers. To address this, we first analyzed the expression of iASPP in patients with acute leukemia (AL) and found it was highly expressed in patients with AL. We further established a transgenic mouse model in which human iASPP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Manually enhanced expression of Since the effect of certain miRNAs on carcinogenesis depends on their downstream targets [24,25], various predictive algorithms were used to calculate target sequences for miR-140 in order to clarify the corresponding reaction chains involved in the inhibition of PDAC's proliferation and metastasis by induction of miR-140. The iASPP oncogene was verified as an important downstream target of miR-140 because of its frequent overexpression in many types of cancer and serves as an essential modulator of cell replication, survival, and migration [26][27][28][29]. Overexpression of miR-140 could downregulate the protein level of iASPP, while knockdown of miR-140 could up-regulate the expression of iASPP.…”
Section: Discussionmentioning
confidence: 99%
“…Manually enhanced expression of Since the effect of certain miRNAs on carcinogenesis depends on their downstream targets [24,25], various predictive algorithms were used to calculate target sequences for miR-140 in order to clarify the corresponding reaction chains involved in the inhibition of PDAC's proliferation and metastasis by induction of miR-140. The iASPP oncogene was verified as an important downstream target of miR-140 because of its frequent overexpression in many types of cancer and serves as an essential modulator of cell replication, survival, and migration [26][27][28][29]. Overexpression of miR-140 could downregulate the protein level of iASPP, while knockdown of miR-140 could up-regulate the expression of iASPP.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of iASPP was shown to improve the efficacy of chemotherapy in cancer treatment [1013]. Epithelial–mesenchymal transition (EMT) plays a key role in facilitating cancer metastasis, and suppression of EMT leads to enhanced sensitivity to chemotherapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Aspp1 contributes to the removal of severely damaged cells from the HSC pool by the induction of apoptosis after severe DNA damage. This is reminiscent of the recent study of iAspp in HSCs and leukemia, which revealed that overexpression of iAspp results in blockage of apoptosis and an increase in the proportion of damaged HSPCs after irradiation (Jia et al, 2014). Thus, the balance among Aspp family members may be critical to the fine-tuned control of DNA damage accumulation in the HSC pool.…”
Section: Discussionmentioning
confidence: 79%